2014
DOI: 10.1016/j.ecoleng.2013.09.069
|View full text |Cite
|
Sign up to set email alerts
|

The River Gelså restoration revisited: Habitat specific assemblages and persistence of the macroinvertebrate community over an 11-year period

Abstract: Please cite this article in press as: Friberg, N., et al., The River Gelså restoration revisited: Habitat specific assemblages and persistence of the macroinvertebrate community over an 11-year period. Ecol. Eng. (2013) b s t r a c tThe study was undertaken on the River Gelså, Denmark, where a 1.8 km meandering course was established in 1989 to replace a channelized river reach. This restoration project was the first of its kind in Denmark and has the longest time-series of post-intervention data of any resto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…These results are consistent with other restoration studies, which indicated that hydromorphological restoration measures increasing structural heterogeneity or restoring natural flow regimes did not generally promote macroinvertebrate biodiversity, even if habitat changes were considerable (Lepori et al, 2005;Jähnig et al, 2010;Palmer et al, 2010;Haase et al, 2013;Friberg et al, 2014). Nonetheless, by employing an alternative approach based on quantification of microhabitat diversity and patchiness rather than restoration per se, we were able to identify some important cases where restoration did have positive effects on macroinvertebrate metrics.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These results are consistent with other restoration studies, which indicated that hydromorphological restoration measures increasing structural heterogeneity or restoring natural flow regimes did not generally promote macroinvertebrate biodiversity, even if habitat changes were considerable (Lepori et al, 2005;Jähnig et al, 2010;Palmer et al, 2010;Haase et al, 2013;Friberg et al, 2014). Nonetheless, by employing an alternative approach based on quantification of microhabitat diversity and patchiness rather than restoration per se, we were able to identify some important cases where restoration did have positive effects on macroinvertebrate metrics.…”
Section: Discussionsupporting
confidence: 81%
“…However, evidence for strong and long-term positive ecological effects of these measures on macroinvertebrates remains generally limited (e.g. Palmer et al, 2010;Feld et al, 2011;Friberg et al, 2014), despite some notable exceptions (Miller et al, 2010;Kail et al, 2015). These findings partly reflect the lack of robust scientific assessments of restoration measures, but even where such assessments have been carried out, changes in invertebrate diversity and community composition have often been minimal (e.g.…”
Section: Introductionmentioning
confidence: 69%
“…Kondolf and Micheli (1995) suggested that the minimum monitoring period to judge the sustainability of a restoration scheme is at least 10 years, based on the argument that a restored site should experience variable climatic events and discharge conditions during the monitoring period. Consequently, monitoring that exceeds 5 years is relatively rare, and a monitoring period of more than 10 years is exceptional (Friberg et al, 2014). Consequently, monitoring that exceeds 5 years is relatively rare, and a monitoring period of more than 10 years is exceptional (Friberg et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the volume of long-term studies able to identify the performance trajectory of stream restoration projects is low, owing primarily to limited project funding that often ceases soon after the restoration work is completed (Champoux et al, 2003;Buchanan et al, 2014). Consequently, monitoring that exceeds 5 years is relatively rare, and a monitoring period of more than 10 years is exceptional (Friberg et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of restoration effects has mainly focused on responses of aquatic organisms, such as fish (e.g., Roni et al, 2008;Haase et al, 2013;Schmutz et al, 2016), benthic invertebrates (e.g., Jähnig et al, 2010;Friberg et al, 2014;Verdonschot et al, 2016), and macrophytes (e.g., Lorenz et al, 2012;Ecke et al, 2016). Recently, increasing attention has also been given to the response of floodplain organisms (e.g., Hering et al, 2015;Göthe et al, 2016;Januschke and Verdonschot, 2016), while functional characteristics, i.e., the rates and patterns of ecosystem processes, have rarely been addressed.…”
Section: Introductionmentioning
confidence: 99%